ANALISIS YURIDIS FREIES ERMESSEN SEBAGAI DASAR KEABSAHAN KEPUTUSAN PEJABAT PEMBINA KEPEGAWAIAN TENTANG DEMOSI (STUDI PUTUSAN NOMOR: 088/G/2014/PTUN.SMG) JURIDIC ANALYSIST ABOUT FREIES ERMESSEN AS DECISION LEGALITY FUNDAMENTAL BY EMPLOYMENT SUPERVISORY OFFICER ABOUT DEMOTION (SEMARANG STATE ADMINISTRATIVE COURT CASE STUDY NUMBER: 088/G/2014/PTUN.SMG) - Arista Jehan Sandy; Tedi Sudrajat; Weda Kupita (Soedirman Law Review, 2020)
This research is sourced from the Semarang State Administrative Court Case Study Number: 088 / G / 2014 / PTUN.SMG, which will elaborate on how the Employment Supervisory Officer authority uses discretionary power in determining demotion decisions, also how the judges determines legal consideration in determining the cancellation of demotion decree that against the discretionary power principle. Defendant in this case is Magelang Regency Regent with lawsuit object is Magelang Regent Decree Number 821.2/123/KEP/13/2014 at 26 September 2014. The method research used in this study is normative juridict with statute approach, case approach, and conceptual approach. The author uses primary legal materials and secondary legal materials with normative legal inventory and scientific literature studies related to research. The legal materials is processed by qualitative data analysis methods with grammatical interpretation, systematic interpretation, and authentic interpretation. Based on this research, discretionary power principle in demotion decree is not in accordance with Legislation Number 30, 2014 that regulate about using discretionary power as decision legality fundamental that use discretionary power, because demotion is rigidly regulated in Government Regulation Number 53, 2010. The Judges decide to cancel the decree because defendant violated his authority as employment supervisory officer, the decree is against the rule of discretionary power, and defendant uses improper legal standing in issuing the decree. Keywords: Discretionary Power, Demotion Decree, State Administrative DecisionLegality